RETRACTED: l-Arginine Uptake by Cationic Amino Acid Transporter Promotes Intra-Macrophage Survival of Leishmania donovani by Enhancing Arginase-Mediated Polyamine Synthesis - Mandal, Abhishek; Das, Sushmita; Kumar, Ajay; Roy, Saptarshi; Verma, Sudha; Ghosh, Ayan Kumar; Singh, Ruby; Abhishek, Kumar; Saini, Savita; Sardar, Abul Hasan; Purkait, Bidyut; Kumar, Ashish; et al. (Frontiers in Immunology, 2017)
The survival of intracellular protozoan parasite, Leishmania donovani, the causative agent of Indian visceral leishmaniasis (VL), depends on the activation status of macrophages. L-arginine, a semi-essential amino acid plays a crucial regulatory role for activation of macrophages. However, the role of L-arginine transport in VL still remains elusive. In this study, we demonstrated that intra-macrophage survival of L. donovani depends on the availability of extracellular L-arginine. Infection of THP-1 derived macrophage/human monocyte derived macrophage (hMDM) with Leishmania, resulted in upregulation of L-arginine transport. While investigating the involvement of the transporters, we observed that Leishmania survival was greatly impaired when the transporters were blocked either using inhibitor or siRNA mediated downregulation. CAT-2 was found to be the main isoform associated with L-arginine transport in L. donovani infected macrophages. L-arginine availability and its transport regulated the host arginase in Leishmania infection. Arginase and iNOS expression were reciprocally regulated when assayed using specific inhibitors and siRNA mediated downregulation. Interestingly, induction of iNOS expression and nitric oxide production were observed in case of inhibition of arginase in infected macrophages. Furthermore, inhibition of L-arginine transport as well as arginase resulted in decreased polyamine production, limiting parasite survival inside macrophage. L-arginine availability and transport regulated Th1/Th2 cytokine levels in case of Leishmania infection. Upregulation of L-arginine transport, induction of host arginase and enhanced polyamine production were correlated with increased level of IL-10 and decreased level of IL-12 and TNF-α in L. donovani infected macrophages. Our findings provide clear evidence for targeting the metabolism of L-arginine and L-arginine-metabolizing enzymes as an important therapeutic and prophylactic strategy to treat visceral leishmaniasis.